Fibrocytes in Chronic Periaortitis: A Novel Mechanism Linking Inflammation and Fibrosis. Issue 11 (30th September 2019) - Nicastro, Maria; Vescovini, Rosanna; Maritati, Federica; Palmisano, Alessandra; Urban, Maria L.; Incerti, Monia; Fenaroli, Paride; Peyronel, Francesco; Benigno, Giuseppe D.; Mangieri, Domenica; Volpi, Riccardo; Becchi, Gabriella; et al.
Abstract : Objective: Chronic periaortitis (CP) is a rare disease characterized by periaortic and periiliac fibroinflammatory tissue. The pathogenic mechanisms leading to tissue accumulation and activation of fibroblasts are unclear. This study was undertaken to explore the role of fibrocytes, circulating precursors of tissue fibroblasts, in patients with CP. Methods: We studied 44 patients with newly diagnosed CP and 30 healthy controls. Circulating fibrocytes were identified as Col1+CD45+ cells using flow cytometry. Retroperitoneal tissue biopsy samples from 9 CP patients were stained with anti–type I procollagen, anti‐CXCR4, and anti‐CD45 antibodies and analyzed by confocal microscopy to detect tissue‐infiltrating fibrocytes. Circulating levels and tissue expression of CXCL12, a CXCR4 ligand that promotes fibrocyte homing, were investigated using enzyme‐linked immunosorbent assay and immunohistochemistry, respectively. We also characterized T helper polarization in biopsy samples from CP patients and measured serum levels of a panel of cytokines that are hallmarks of T helper responses and capable of influencing fibrocyte differentiation. Results: The frequency of circulating Col1+CD45+ fibrocytes was higher in patients than in controls ( P = 0.0371). CD45+proCol1+ and CXCR4+proCol1+ cells were detected in all examined biopsy samples from CP patients. Serum levels of CXCL12 were also higher in CP patients than controls ( P = 0.0056), and tissue‐infiltrating inflammatory cells intensely expressed CXCL12. Increased serum levels of Th2 cytokines (e.g., interleukin‐13 [IL‐13] and IL‐10) were found in patients, and immunohistochemistry revealed a dominant infiltration of GATA‐3+ cells, also indicating Th2 polarization; Th2‐skewed responses are known to promote fibrocyte differentiation. Conclusion: Our findings indicate that fibrocytes are enriched in the peripheral blood of CP patients and infiltrate target lesions. The accumulation of fibrocytes in the pathologic tissue might be driven by CXCL12, and Th2‐skewed immune responses are likely to facilitate their differentiation.